The difference of gut microbiome in different biliary diseases in infant before operation and the changes after operation - Xinhe Sun; Yaoyao Cai; Wenwen Dai; Weiwei Jiang; Weibing Tang (BMC, 2022)
Abstract Background Evidence supports an association between cholestatic liver disease and changes in microbiome composition. Nevertheless, the identification of this special type of biliary atresia from non-biliary atresia cholestasis is still a major clinical difficulty. The purpose of this study is to compare the differences in the composition of gut microbiome between infants with biliary atresia and infant with non-biliary atrestic cholestasis, to find new ways to identify and diagnose these two diseases early, to understand the influence of the presence or absence of bile on the composition of the gut microbiome in infants with cholestasis. Methods Using 16S rDNA gene sequencing technology to analyze the intestinal flora of the participants. Results In terms of diversity, there is an obvious structural separation in the intestinal microbiota of the BA group and the CD group, and this structural separation also exists in the comparison between the two groups before surgery. Taxonomic analysis demonstrated that the two groups showed an increase in Proteobacteria and Firmicutes before surgery, and the relative abundance of potential pathogens such as Shigella, Streptococcus, Klebsiella, etc. increased, potential probiotics such as Bifidobacteria and Lactobacillus decreased, but the relative abundance of each genus was different between groups. It was found that Enterococcus, Ralstonia, Nitriliruptoraceae, etc. were differentially enriched in the BA group, the CD group are mainly enriched in Veillonella, Clostridium_sensu_stricto_1 and Lactobacillus. Functional analysis of the groups showed that the BA group mainly focused on the processes of energy release processes, and the CD group mainly focused on the biosynthesis of amino-acids to consume energy. Conclusions The composition of intestinal flora is different between biliary atresia and non-biliary atretic cholestasis. Enterococcus, Ralstonia, etc. may become biomarkers for the identification and diagnosis of both.